Aminoff's neurology and general medicine. - Aminoff, Michael J. (Michael Jeffrey); Josephson, Scott Andrew (Elsevier/AP, 2014)
Aminoff's Neurology and General Medicine is the standard and classic reference providing comprehensive coverage of the relationship between neurological practice and general medicine. As neurologists are asked to consult on general medical conditions, this reference provides an authoritative tool linking general medical conditions to specific neurological issues and disorders. This is also a valuable tool for the general practitioner seeking to understand the neurological aspects of their medical practice. Completely revised with new chapters covering metastatic disease, bladder disease, psychogenic disorders, dementia, and pre-operative and post-operative care of patients with neurologic disorders, this new edition will again be the go-to reference for both neurologists and general practitioners.